Youth perception and intention towards entrepreneurship on online business / Muharratul Sharifah Bt Shaik Alaudeen and Yong Azrina Aliakbar - Shaik Alaudeen, Muharratul Sharifah; Aliakbar, Yong Azrina (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2012)
The advancement of internet technologies provide opportunity to people around the world to run business through online by having website, blog and online social network such as Facebook. Even big corporations have websites and Facebook accounts to spur online business. Online business became popular method to earn income as well as promotion and advertising methods in a business.